Tumor biology: molecular genetics mechanisms of initiation, promotion and progression - Ageeva, Elizaveta; Golubinskayaa, Elena; Makalish, Tatyana; Fomochkina, Iryna; Kubyshkin, Anatolii; Zukow, Walery; Shramko, Iuliana; Ostapenko, Olga; Zhukova, Anna; Gurtovaya, Anna (Journal of Education, Health and Sport, 2022)
For all tumors, regardless of type and tissue, there are a number of common features. These include high proliferative activity, disturbances in the mechanisms of apoptosis and "invisibility" for the cells of the immune system. At the basis of all these disorders lies a malfunction in the interaction between signaling proteins inside the cell, due to a violation of the expression of genes responsible for their synthesis. The aim of the review is to study the molecular biological mechanisms of carcinogenesis, characteristics and features of tumor cells that affect the development of the disease, progression, drug resistance and clinical results and the possibilities of targeted therapy of oncological diseases. Material and methods. The search for literature sources was carried out using PubMed, CyberLeninka, eLibrary, Google Scholar databases; the search depth was 15 years. Results. Recent works have shown the evolution of views on the classification of tumors from the point of view of the mechanisms of damage to the processes of cellular regulation and histogenesis, as well as the development of the modern theory of carcinogenesis, ideas about the mechanisms of development of tumor diseases and the prospects of modern therapies. Conclusion. The study of molecular biological mechanisms of carcinogenesis, characteristics and features of tumor cells is not only fundamental, but also of applied importance in order to predict the development of the disease, progression, drug resistance, clinical results and the possibilities of targeted therapy.